2014
DOI: 10.1177/0734242x14525822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrolysis temperature on the physicochemical properties of empty fruit bunch and rice husk biochars

Abstract: Biochar has received great attention recently due to its potential to improve soil fertility and immobilize contaminants as well as serving as a way of carbon sequestration and therefore a possible carbon sink. In this work, a series of biochars were produced from empty fruit bunch (EFB) and rice husk (RH) by slow pyrolysis at different temperatures (350, 500, and 650°C) and their physicochemical properties were analysed. The results indicate that porosity, ash content, electrical conductivity (EC), and pH val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
134
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(177 citation statements)
references
References 33 publications
22
134
3
6
Order By: Relevance
“…Sun et al also found a decrease in the concentration of Ca and Mg as the pyrolysis temperature increased from 450 to 600 • C using hickory wood as feedstock [21]. Thus, both the volatility of the nutrients and the influence of temperature on the composition and chemical structure of biochar can significantly affect the concentration of nutrients during the process [13].…”
Section: Elemental and Nutrients Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Sun et al also found a decrease in the concentration of Ca and Mg as the pyrolysis temperature increased from 450 to 600 • C using hickory wood as feedstock [21]. Thus, both the volatility of the nutrients and the influence of temperature on the composition and chemical structure of biochar can significantly affect the concentration of nutrients during the process [13].…”
Section: Elemental and Nutrients Analysismentioning
confidence: 99%
“…As the pyrolysis temperature increased, FTIR spectra of biochars revealed a decrease in the stretching of O-H (3200-3500 cm −1 ) and C-H (2935 cm −1 ) [13], this was attributed to the acceleration of dehydration reaction in biomass [30], which suggested a decrease in the polar functional groups with an increase in pyrolysis temperature [50]. In particular, biochars began to increase aromatic C=C stretching (1440 cm −1 ) [29] and out-of-plane deformation by aromatic C-H groups (885 cm −1 ) [51], while the symmetric C-O stretching (1030-1110 cm −1 ) for the source material began to disappear with the increasing pyrolysis temperature [51].…”
Section: Fourier-transform Infrared Analysis and Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of the nutrients in the biochars with increasing temperature is due to their volatility and effect of pyrolysis temperature on both composition and chemical structure of biochars. Besides the concentration of the nutrients in the biochar also depend on the process of partial devolatilization of the nutrients at elevated temperatures [9].…”
Section: Resultsmentioning
confidence: 99%